Re-thinking Indoctrination in Education: a Philosophical Enquiry into the Consensus and Conflict (2021)
Education as a tool for national development hinges on adopting the right educational philosophy. The type of education a country adopts is of great importance in the achievement of the goals and philosophies of her education as spelt out in the educational policy. Based on the premise that school children are prone to indoctrination as a result of their impressionable ages, the study examined critically the concept of indoctrination and properly analyse its place in the contemporary Nigerian society. The methodology involves speculating, analysing and prescribing, to explain the concept of indoctrination and education as well as how to eliminate the use of indoctrination in Nigeria's education system. Based on the findings of the study, it is necessary for the teacher to eliminate the use of indoctrination and create a democratic classroom in order to implement the goals and philosophy of Nigerian education. The study recommended that stake holders in the education industry should discourage indoctrination by providing proper guidance and monitoring of schools to ensure compliance.